Roles of DNA damage in renal tubular epithelial cells injury - Wang, Peipei; Ouyang, Jing; Jia, Zhanjun; Zhang, Aihua; Yang, Yunwen (Frontiers in Physiology, 2023)
The prevalence of renal diseases including acute kidney injury (AKI) and chronic kidney disease (CKD) is increasing worldwide. However, the pathogenesis of most renal diseases is still unclear and effective treatments are still lacking. DNA damage and the related DNA damage response (DDR) have been confirmed as common pathogenesis of acute kidney injury and chronic kidney disease. Reactive oxygen species (ROS) induced DNA damage is one of the most common types of DNA damage involved in the pathogenesis of acute kidney injury and chronic kidney disease. In recent years, several developments have been made in the field of DNA damage. Herein, we review the roles and developments of DNA damage and DNA damage response in renal tubular epithelial cell injury in acute kidney injury and chronic kidney disease. In this review, we conclude that focusing on DNA damage and DNA damage response may provide valuable diagnostic biomarkers and treatment strategies for renal diseases including acute kidney injury and chronic kidney disease.